Penerapan Project Based Learning (PjBL) Terbimbing untuk Meningkatkan Keaktifan dan Pemahaman Siswa pada Konsep Momentum, Impuls, dan Tumbukan - Lisa Puspitasari; Budi Astuti; Masturi Masturi (Faculty of Science and Education, UIN Walisongo Semarang, 2020)
This study aims to analyze the increase in students' activeness and conceptual understanding after the guided Project Based Learning (PjBL) model is applied. The research method used was a pre-experimental one group pretest-postest design. The research instruments included test and non-test instruments. The test instrument in this study was a reasoned multiple choice. The non-test instrument uses student activeness observation sheets. Students' activeness and conceptual understanding were analyzed using the N-Gain test. The significance of increasing students' activeness and understanding of concepts was analyzed using the Wilcoxon mathced pairs test. The results of the data analysis showed that the students' activeness and conceptual understanding of the Momentum, Impulse, and Collision material after being applied to guided PjBL experienced a low increase with N-Gain of 0.20 and 0.22. The results of the significance test of students' activeness and conceptual understanding were obtained values of 0.041 and 0.000 (0.050). Based on the results of the analysis, it can be concluded that the implementation of the guided Project Based Learning model was able to significantly increase the activeness and understanding of students' concepts in the material Momentum, Impulse and Collision at Nurul Islami High School.